The plant bug subfamily Phylinae in Japan, with key to genera and descriptions of eight new species (Hemiptera: Heteroptera: Miridae) - Yasunaga, Tomohide (Zootaxa, 2022)
The Japanese phyline fauna is reviewed and updated; 127 species referred to 37 genera are now recognized. Eight new species in five genera, namely Eremophylus Yasunaga, Europiella Reuter Orthonotus Stephans, Pityopsallus Wagner and Psallus Fieber, are herein described as new to science. The genus Eremophylus, now considered to have a close relationship to Europiella Reuter, is proposed to be placed in the subtribe Oncotylina of the tribe Phylini, and four other genera treated herein are re-diagnosed or discussed. The female of Eremophylus hirtus Yasunaga is documented for the first time, with a detailed description of the female genitalia. Europiellomorpha Duwal is synonymized with Europiella, and eight Asian species of Pityopsallus are also transferred from Psallus Fieber. A key and checklist for all known Japanese genera are provided.